The Experiential Self Re-Creates Itself in Others via the Enlargement of the Self’s Space-Control Ability: Dan Zahavi’s Arguments for the Existence of the Self - Trung, Đỗ Kiên (Labyrinth, 2019)
The diversity and complexity of the arguments and criticisms among philosophers on the question of the actual existence of the self can be condensed into two contrasting issues: The self is an experienced phenomenon that is generalized into a concept to assign to the cognitive subject as a tool for identification, or the self has its own existence as a transcendental entity that is activated and developed through interactions between the cognitive subject and the environment. Dan Zahavi summed up the endless controversy over the formation of the self in phenomenology, existentialism, and new insights in neuroscience to conclude that the existence of the self is only meaningful when it is "the experiential self." My article will focus on two issues: firstly, the self is formed by the interaction between the subject and the object in which the object is actively engaged in the control space of the subject; secondly, the understanding of the subject’s self-perception process, through the perspective of neuroscience, is triggered by the subject seeing itself in the other person.